Nutritional support and therapy in pancreatic surgery: a position paper of the International Study Group on Pancreatic Surgery (ISGPS) - Gianotti, Luca; Hackert, Thilo; Probst, Pascal; Büchler, Markus W. (Surgery, 2018)
Background: The optimal nutritional therapy in the field of pancreatic surgery is still debated. Methods: An international panel of recognized pancreatic surgeons and pancreatologists decided that the topic of nutritional support was of importance in pancreatic surgery. Thus, they reviewed the best contemporary literature and worked to develop a position paper to provide evidence supporting the integration of appropriate nutritional support into the overall management of patients undergoing pancreatic resection. Strength of recommendation and quality of evidence were based on the approach of the grading of recommendations assessment, development and evaluation Working Group. Results: The measurement of nutritional status should be part of routine preoperative assessment because malnutrition is a recognized risk factor for surgery-related complications. In addition to patient's weight loss and body mass index, measurement of sarcopenia and sarcopenic obesity should be considered in the preoperative evaluation because they are strong predictors of poor short-term and long-term outcomes. The available data do not show any definitive nutritional advantages for one specific type of gastrointestinal reconstruction technique after pancreatoduodenectomy over the others. Postoperative early resumption of oral intake is safe and should be encouraged within enhanced recovery protocols, but in the case of severe postoperative complications or poor tolerance of oral food after the operation, supplementary artificial nutrition should be started at once. At present, there is not enough evidence to show the benefit of avoiding oral intake in clinically stable patients who are complicated by a clinically irrelevant postoperative pancreatic fistula (a so-called biochemical leak), while special caution should be given to feeding patients with clinically relevant postoperative pancreatic fistula orally. When an artificial nutritional support is needed, enteral nutrition is preferred whenever possible over parenteral nutrition. After the operation, regardless of the type of pancreatic resection or technique of reconstruction, patients should be monitored carefully to assess for the presence of endocrine and exocrine pancreatic insufficiency. Although fecal elastase-1 is the most readily available clinical test for detection of pancreatic exocrine insufficiency, its sensitivity and specificity are low. Pancreatic enzyme replacement therapy should be initiated routinely after pancreatoduodenectomy and in patients with locally advanced disease and continued for at least 6 months after surgery, because untreated pancreatic exocrine insufficiency may result in severe nutritional derangement. Conclusion: The importance of this position paper is the consensus reached on the topic. Concentrating on nutritional support and therapy is of utmost value in pancreatic surgery for both short- and long-term outcomes.
Gesehen am 05.04.2019